Diagnóstico socio económico ambiental de la Comunidad Nativa Copal Urco, distrito del Napo, Maynas, Loreto, 2022 - Pinedo Diaz, Karla Adilia (2024)
The present study has been developed in the native community of Copal Urco, Loreto region, with the purpose of determining the current state of the socioeconomic activities of the village. From the results obtained, they present economic activity based on hunting, fishing and gathering, as well as planting of some food products. The timber activity has been paralyzed due to the lack of support from the state. Likewise, the socioeconomic level of the community members is among the lowest, 92% of the residents are located in levels C and D. In that sense, the residents have not resolved the problem of ownership of the land and the population. It does not have the minimum basic services for human survival, occupying the lowest levels of the Human Development Index. The population of Copal Urco is an unemployed population and has no interest in working because the state allows certain types of subsidies and there is no concern among the community members about the issue of abundant illegal logging. It is necessary to establish strategic alliances between institutions to improve the few services that the state provides to the community.